PERENCANAAN BISNIS KANTOR AGEN PROPERTI RUMAH IMPIAN AGENCY - Meri Linawati Tanuwidjaja; Meriza Hendri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The property industry in the Greater Bandung area has shown significant growth, driven by the high demand for housing. Rumah Impian Agency emerges as a solution by integrating digital and personalized services in property marketing. This study aims to develop a business plan by analyzing market, financial, operational, and marketing strategy aspects. A qualitative method was used, with data collected through observation and secondary data analysis from industry reports and official statistics. The Business Model Canvas (BMC), SWOT analysis, and the Timmons entrepreneurial model were employed to evaluate business feasibility. The results indicate that the market growth rate reaches 18% annually. From the financial aspect, the Net Present Value (NPV) is positive at IDR 2,096,296,000, the Profitability Index (PI) is 2.77, the Internal Rate of Return (IRR) is 106%, and the Payback Period (PP) is 7.89 months, indicating high investment feasibility. The Gross Profit Margin is 50.09%, Net Profit Margin is 40.07%, and Return on Investment (ROI) stands at 217%, reflecting strong profitability efficiency. Rumah Impian Agency demonstrates promising business potential with a large market opportunity and solid financial performance. Digital marketing and technology-based services are the agency’s main strengths in facing competition. It is recommended that the company strengthen its digital marketing strategies, establish partnerships with property developers and financial institutions, and enhance after-sales services to build customer trust and loyalty. With the right strategies, Rumah Impian Agency has the potential to become a leading property agency in the region.